Development of an Internet of Things (IoT)-Based System for Monitoring Planthopper Populations and Rice Field Microclimate to Support the Hb Design of Integrated Pest Management in Rice Cultivation - Maimuna Nontji; Anita Ninasari; Aulia Brilliantina; Muzakir; Emilia Oktara (Agriculture Journal, 2026)
The escalating volatility of Nilaparvata lugens (Brown Planthopper) populations threatens national rice sovereignty and necessitates proactive pest management strategies. This research developed an Internet of Things (IoT)-based architecture integrating terrestrial microclimatic sensors with satellite-based vegetation indices across 4,500 hectares of paddy fields in Indramayu Regency. Fifteen LoRaWAN-enabled sensor nodes achieved 98.45% data transmission integrity. The system detected humidity-driven population surges (>85% RH for 72 hours) four days earlier than conventional visual observations. ANOVA analysis confirmed significant spatial positioning effects (F(2, 42) = 15.67, p = .001). In addition, monitored plots demonstrated 1.4 tons/Ha higher grain yields and a 30% reduction in pesticide costs compared to traditional farming. The integration of sensor thermodynamics with BRIN NDVI data establishes a technically viable blueprint for Agriculture 4.0. These findings provide empirical evidence that precision digital interventions can enhance food production resilience in Indonesia.